Metadata Standards: a Review Towards Modeling Experiments - Santana, Filipe A.; Cordeiro, André F. R.; OliveiraJr, Edson (Anais da Escola Regional de Engenharia de Software (ERES); 2023: Anais da VII Escola Regional de Engenharia de Software, 2023)
Metadata consists of elements that describe specific content of data. When structured according to standards, they contribute to data interoperability. This study presents a secondary study, a Systematic Mapping (SM), to search for metadata patterns that can be used in the field of Computer Science (CS), especially in the subjects of Software Engineering (SE) and Information Systems (IS). At the end of the search string execution, 43 studies were analyzed. Of these, 23 studies were selected. Based on the observed results, a promising research area is identified, focusing on the adoption of metadata standards in various activities within the context of CS, SE, and IS.